Full moment-deflection response and bond stiffness reduction of RC elements strengthened with prestressed FRP materials. (15th March 2021) - Slaitas, Justas; Valivonis, Juozas
Abstract: Despite the benefits of strengthening reinforced concrete (RC) structures with fibre reinforced polymer (FRP) materials, there is a lack of design recommendations for evaluating the effect of prestressing. Also, all the benefits of the repair can be compromised by not full composite action of concrete and FRP. Therefore, contact stiffness reduction factor is derived and the use of it for a prediction of full bending moment-deflection response is presented in a current paper. The proposed calculation model includes situations, when the RC member was strengthened under external load action and prestressing force was applied to the FRP material – a common situation in practice. Furthermore, a test program is presented to support the theoretical model, consisting of 13 reinforced concrete beams, strengthened with prestressed CFRP laminates. In order to imitate common situation in practice, half of the specimens were strengthened under external load action. Additional results of 73 reinforced concrete beams strengthened with externally bonded (EBR) and near surface mounted (NSM) CFRP and GFRP sheets, laminates and rods were taken from various scientific publications. The numerical results were in a good agreement with experimental ones.